Privatizing the Welfare State: Nonprofit Community-Based Organizations as Political Actors - Marwell, Nicole P. (American Sociological Review, 2004)
This paper examines a form of state social provision that has been neglected by current sociological theory: publicly funded supportive services. Federal policies of privatization and devolution, embraced since the Reagan years, have made private, nonprofit organizations the primary deliverers of these services. Public supportive services are distributed via competitive state- and local-level allocative processes that send government contracts to specific nonprofit community-based organizations (CBOs), which in turn serve specific neighborhoods and individuals. I describe a model by which CBOs generate greater contract revenues by adding electoral politics to their more traditional roles of providing services and building communities. This model produces a new kind of CBO: the machine politics CBO. By reciprocally distributing services to residents and binding residents to the organization, machine politics CBOs create reliable voting constituencies for local elected officials. These officials trade these constituencies at higher levels of the governmental system and steer government human service contracts to favored CBOs. Through this process, nonprofit CBOs can influence the allocation of service-based social provision in cities and therefore impact individuals' ability to access these services.